METHODS, FORMS AND MEANS OF COMPETENCE -BASED APPROACH TO ORGANIZING THE EDUCATIONAL PROCESS IN HIGHER EDUCATION - Anarqulova Gulnaz Mirzakhmatovna (Journals Park Publishing, 2025)
The article examines the mechanism of the competence-based approach to organizing the educational process in higher education, types of competencies and methods of their implementation, as well as the differences between competence and competency.
Keywords: Competence, competency, higher education, educational process, professional and pedagogical competence.